The Use of The Dictation Strategy to Improve The Listening Skill of The Tenth-Grade Students at SMAS Santo Gabriel Maumere - Fua, Antonius Prisko Virgo; Janggo, Wendelinus Oscar; Sina, Maria Wisendy (LPPPI Publishing, 2025)
This study explores the effectiveness of dictation techniques in enhancing the listening skills of tenth-grade students at SMAS Katolik Santo Gabriel Maumere. Recognizing the significance of English as a global language and Indonesian learners' challenges, the research employs a classroom action research design comprising two cycles. The data collection method included observations, questionnaires, interviews, and tests. Initial findings revealed that no one student met the success criteria for listening test in pre-cycle. In cycle 1, the result of test show that only 54,54% students meet the success criteria. After making the Cycle 1, indicating low interest and engagement in learning English. In response, the researcher-teacher implemented modifications in Cycle 2, such as clearer instructions, increased student engagement, and the use of audio recordings. This led to a remarkable improvement, with 90,90% of students achieving the success criteria. The study concludes that the dictation method, when effectively applied, significantly enhances students listening abilities and overall engagement in the learning process. Recommendations for educators are provided to encourage the adoption of similar strategies to foster improved listening skills among students.